CALCULATION OF THERMAL STRESS ON SOLID SURFACE IN ELASTOHYDRODYNAMIC LUBRICATION OF LINE CONTACT - LU ZunYou; LV YanJun (Jixie qiangdu)
In line contact thermal elastohydrodynamic lubrication,changes of temperature rise are generated on the two solid surfaces in contact with oil film,and the thermal stresses of the two solid surfaces are bound to be generated. The solid surfaces are constrained by the non-uniformly distributed oil film pressure. It is difficult to solve the thermal stresses on solid surfaces numerically. Both the theory of thermoelasticity and the principle of heat and pressure conversion were introduced into the line contact thermal elastohydrodynamic lubrication,and the numerical method was given to realize the numerical solution of linear expansion coefficients of solid surfaces and solve the numerical calculation of thermal stress and thermal elastic deformation.The numerical results of both the lubrication characteristics and the thermal stresses satisfying the convergence precision were obtained and the influence of the linear load changes on the thermal stresses were discussed by some examples. The research contents could provide reference for thermal elastohydrodynamic lubrication analysis and solid thermal stress analysis under constrained conditions.